The Implementation of Halal Certification on Imported Agricultural Food Products and Their Relation to International Trade: - - Retno Catur Kusuma Dewi; Mohammad Choirul Anam; Dien Nufitasari (Universitas Merdeka Madiun, 2024)
Abstract Introduction to the Problem: Import activities are strongly related to international trade that one of the objectives is to meet the needs of a country. Indonesia carries out import activities on processed food products and agricultural products in order to fulfill food needs. To protect Indonesian consumers who are predominantly Muslim, Indonesia has passed legislation regarding halal certification and labeling through Law Number 33 of the year 2014 concerning Halal Product Assurance. Purpose/Study Objectives: The problems studied in this study include: (1) How is the implementation of Law Number 33 of 2014 concerning Halal Product Assurance in Halal certification and labeling of imported processed food products and imported agricultural products in Indonesia and (2) How is harmonized Law Number 33 of 2014 concerning Halal Product Assurance, especially on halal certification and labeling of imported processed food products and imported agricultural products in Indonesia related to the Technical Barriers to Trade agreement?. Design/Methodology/Approach: The research method used is juridical-normative with the data sources obtained in the form of primary legal materials in the form of laws and regulations, GATT 1994, and the TBT Agreement, secondary legal materials including legal books and journals, and tertiary legal materials, such as legal dictionaries. Findings: The implementation of Law Number 33 of 2014 has changed the provisions regarding halal certification and labeling of products circulating and traded in Indonesia, including imported processed food products and imported agricultural products, to become mandatory. The conformity of the Law Number 33 of 2014 which is included in technical regulations with the TBT Agreement is an urgency to ensure that national regulations and/or policies do not become obstacles in international trade. Paper Type: Research Article.